Analisis Faktor-faktor yang Mempengaruhi Keefektifan Pengembangan Sistem Informasi - Purnamasari, Dian Indri (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
At present technology is rapidly advancing. It is accompanied by the development of the technology based information system. The development of the information system requires various supporting factors, which are among others the participation of users. This study examines the participation of users, communication of users, top management involvement, complexity of systems, and structure of organizations have influence the successful information system development. The analysis indicates that the participation of users, communication of users, complexity of systems, and structure of organizations statistically did not influence the successful information system development and top management involvement statistically influenced the successful information system development.